Cimifrigines A–G, cytotoxic triterpenes with an oxime group from the flowers of Cimicifuga frigida. Issue 61 (7th August 2017) - Nian, Yin; Yan, Hui; Li, Xiao-Nian; Zhou, Lin; Qiu, Ming-Hua
Abstract : Seven new dahurinol-type triterpene derivatives, including three aglycones, cimifrigines A–C (1–3 ), and four glycosides, cimifrigines D–G (4–7 ), were purified from the flowers of Cimicifuga frigida . Abstract : Seven new dahurinol-type triterpene derivatives, including three aglycones, cimifrigines A–C (1–3 ), and four glycosides, cimifrigines D–G (4–7 ), were purified from the flowers of Cimicifuga frigida . These triterpenoids are characterized by an oxime group at C-15. Spectroscopic analyses and X-ray crystallography were used to determine the new structures. In the in vitro cytotoxicity screening, glycosides (4–7 ) exhibited more noticeable activities than the aglycones (1–3 ) against human HL-60, SMMC-7721, A549, MCF-7, and SW-480 cell lines. Interestingly, compounds5 and7, bearing a 2′- O -acetyl moiety on the sugar unit, showed comparable cytotoxicities to the positive control, cisplatin (IC50 : 0.5 to 5.4 μM). Whereas, analogues4 and6, without the 2′- O -acetyl group, indicated weaker activities with IC50 values ranging from 8.9 to 14.3 μM.